End-to-end simulation environment for mobile edge computing - Gilly, Katja; Bernad, Cristina; Roig, Pedro J.; Alcaraz, Salvador; Filiposka, Sonja (Elsevier BV, 2022)
Performances analysis of resource management techniques and algorithms for edge computing is a crucial step that reveals the effectiveness of edge service placement and migration strategies in terms of delay and usage. To be able to gauge how different optimisations affect the end user quality of experience a holistic approach is needed, so that the end-to-end delay can be measured in a combined setup where the edge infrastructure is integrated in the 5G system architecture. For these purposes we put forward an open source workflow based on the integration of proven simulators as SUMO, OMNeT++ and CloudSim, that will provide the means to create large scale urban mobile simulation environments. This paper discusses the benefits and challenges of such an approach, and provides example results that showcase a few aspects of the potential end-to-end delay analysis by processing the gathered simulation output.
Keywords: 5G mobile communication; Edge computing; End-to-end delay analysis; Simulation; Workflow